Arbuscular mycorrhizal fungi improve legume seedling performance as the competition with conspecific neighbouring adult plants decreases - Chippano, Tomás Adrián (2022)
In temperate grasslands, the balance between competitive and facilitative interactions between adult plants and conspecific seedlings can be affected by defoliation intensity, soil nutrient deficiency and arbuscular mycorrhizal fungi (AMF). Here, we investigated the effect of AMF on the interactions between Lotus tenuis Waldst. & Kit. seedlings grown in the presence or absence of conspecific adult plants defoliated at different intensities (0, 50 and 75%) in a P-deficient soil of the Salado River Basin (Argentina). Mycorrhizal seedlings grown near defoliated and non-defoliated adult plants produced less shoot dry weight (DW) than non-mycorrhizal counterparts, whereas mycorrhizal seedlings alone showed 258% and 504% more shoot DW and shoot P content, respectively than non-mycorrhizal counterparts. This was associated with higher growth and P uptake of mycorrhizal adult plants than non-mycorrhizal counterparts. The competition index between seedlings and adult plants showed competition interaction in mycorrhizal systems (from −2.6 to −1.9) and neutral interaction in non-mycorrhizal systems (near to zero) despite the defoliation intensity. We propose that moderate defoliation (50%) allows maintaining high mycorrhizal benefits in adult plants (110.1% and 168.8% mycorrhizal growth and P response, respectively), whereas high defoliation (75%) decreases mycorrhizal benefits (27.18% and 80.21% mycorrhizal growth and P response, respectively). We highlight AMF symbiosis as an important strategy of L. tenuis adult plants to regulate the growth of neighbouring conspecific seedlings in a P-deficient soil.